Fabrication and Characterization of Cu/SiC‐Based Axially Functionally Graded Beam. Issue 5 (19th January 2022) - Kumar, Viwek; Kumari, Poonam
Abstract : Metal−ceramic based functionally graded materials (FGMs) are mainly used for thermal and structural applications in industry. A metal matrix‐based axially FGM beam is fabricated using a powder metallurgy manufacturing process. The main objective of this work is to develop a processing method for an axially graded beam made of Cu/SiC by stacking powder in the longitudinal direction. A three‐layered Cu/SiC FGM having a step‐wise gradation along the length is fabricated. The green specimens are prepared by the uniaxial compaction of powder mixture by the universal testing machine (UTM) followed by cold isostatic pressing (CIP). Further, a detailed microstructure analysis of the powders and the sintered specimens is conducted. The Vicker's microhardness test is also performed for each layer of the sintered specimen to analyze the effect of SiC content. A smooth transition of the ceramic content in the specimen along the length is observed. The effect of ball milling on the crystallite size is studied using Scherrer and Williamson−Hall approach. An uniform and consistent distribution of the SiC particles shows a reduction in porosities and increment in the hardness value with increase in SiC wt% is also observed. The present investigation helps to design functionally graded rotor blades, gears, and orthopedic implants. Abstract : A Cu−SiC‐based FGM beam having gradation along the length is fabricated through a powder metallurgy technique. A detailed microstructure and microhardness investigation is conducted. A smooth transition of the FGM layers and mechanical properties within the specimen is observed. This work helps to fabricate will help in the fabrication of axially graded gas turbine blades, gears, bearing, and orthopedic implants for futuristic applications.